Bud rot disease of coconut in relation to endemic spots in Kerala state, India - A.R. Rasmi; ROHINI IYER, Rohini Iyer (International Coconut Community, 2005)
In India bud rot is quite common on the West and East Coast tracts. A random survey on bud rot disease of coconut, caused by Phytophthora palmivora But.l, carried out in Kasaragod, Kannur and Calicut districts of Kerala revealed that, there is correlation between the disease incidence and the location of the palms. The disease incidence was high in the hilly tracts when compared to that of the plains. Studies on the survival of P. palmivora propagules in nature revealed that the pathogen survives in the crown, soil and roots of healthy and diseased palms. However, the percentage of survival was high in the endemic areas-Mandapam (Kasaragod District), Josegiri (Kannur Dist.) and Kuttiadi (Kozhikode Dist.), both in the case of diseased and healthy palms compared to that of areas with lesser disease incidence. The temperature and humidity in the coconut growing tracts of hilly areas of Kasaragod, Kannur and Kozhikode districts are suitable for the survival of the pathogen in the crown during almost all months, resulting in the high frequency of disease incidence during monsoon season and continued infection up to January. Examination of the rain water collected from bud rot affected coconut gardens also indicated that the pathogen surviving in the crown debris can act as a source of inoculum, which spreads to the neighboring palms through rain splashes. Based on the weather data it is possible to predict the bud rot incidence well in advance.